LARIISA: an Intelligent Platform to Help Decision Makers in the Brazilian Health Public System - Andrade, Luis Odorico M.; Valter, Raimundo; Ramos, Ronaldo; Vidal, Vania; Andrade, Daniel; Oliveira, Mauro (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2019)
LARIISA is an intelligent framework for decision-making in public health systems. The project had its initial ideas conceived in 2009. Since then it has evolved in the academic and market perspective, becoming a product in 2018 called GISSA. This article presents the architectural evolution of LARIISA, the functionalities implemented, the scientific and commercial results achieved with GISSA. Ontology and Data Mining (DM) are technologies that support their inference mechanisms. A semantic portal is proposed for GISSA and a DM application is presented.